2016
DOI: 10.1213/ane.0000000000001293
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Suppresses Lung Cancer Cell Proliferation Through the Interaction with Opioid Growth Factor Receptor

Abstract: Lung cancer tissues and cell lines express OGFR. Morphine interacts with OGFR and may suppress lung cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 25 publications
4
37
0
1
Order By: Relevance
“…Even though opioids were often found to have pro-proliferative effects on cancer cells, other reports brought opposing findings (Tegeder et al 2003;Tegeder and Geisslinger 2004;Chen et al 2008;Lazarczyk et al 2010;Lennon et al 2014;Gonzalez-Nunez et al 2014;Kim et al 2016). This discrepancy in results stems from different opioid types, cell lines, modes and scheme of administration and probably other factors in a particular study.…”
Section: Discussionmentioning
confidence: 99%
“…Even though opioids were often found to have pro-proliferative effects on cancer cells, other reports brought opposing findings (Tegeder et al 2003;Tegeder and Geisslinger 2004;Chen et al 2008;Lazarczyk et al 2010;Lennon et al 2014;Gonzalez-Nunez et al 2014;Kim et al 2016). This discrepancy in results stems from different opioid types, cell lines, modes and scheme of administration and probably other factors in a particular study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was shown that opioids inhibit MCF7 cell growth in an estrogen-dependent manner [ 69 ]. In addition, MCF7 cells express the opioid-growth factor receptor (OGFr) [ 71 ], which contributes to morphine-induced suppression of lung cancer cell proliferation [ 72 ]. In another study, induction of pro-apoptotic death in SH-SY5Y cells by morphine was opioid-receptor independent and occurred via JNK-ROS-mitochondria-dependent apoptosis signaling [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported that morphine can reduce the efficacy of chemotherapy, stimulating tumor cell growth in brain, breast and renal cancer [ 22 , 23 , 24 , 25 ]. Other reported that the association of morphine with chemotherapeutic agents result in an improved antitumor effect and suppression of cancer cells proliferation [ 26 , 27 ]…”
Section: Introductionmentioning
confidence: 99%